(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
Massage is an effective method used by many people to get a noticeable effect of feeling comfortable and relaxed in light of the current life and problems, as massage contains regular strokes and pressure on the tissues inside the body to obtain complete relaxation through the researcher’s observation of the activities of the field and the track and noting the functional changes that occur during training, including the occurrence of severe fatigue among the players and a decrease in the level of performance when playing. From here lies the problem of the research in treating cases of fatigue that occur through the use of vibration massage and some relaxation exercises to improve functional variables and reduce fatigue, as the research objectives were determined by identifying the functional variables and the fatigue index among the college team players in the track and field for the pre- and post-tests, identifying the differences between the preand post-tests for the functional variables and the fatigue index among the college team players in the track and field, as the research hypotheses were determined that there are statistically significant differences between the pre- and post-tests for the functional variables of the college team players in the track and field. There are statistically significant differences between the pre- and post-tests to reduce fatigue for the college team players in the track and field. The researcher used the experimental method, as choosing the method is a necessity of scientific research, as it must be compatible with the nature of the problem to be solved in order to reach the required results. The research community was determined, which was the female players of the College of Physical Education and Sports Sciences for Girls team in track and field, numbering (5) players. The researcher used the following tests: (pulse - blood pressure measurement - vital capacity test - fatigue equation). The researcher concluded: The exercises used and massage have a positive effect in improving the pulse and vital capacity. The exercises used and massage have a positive effect in reducing fatigue. The researcher recommended emphasizing functional changes and how to develop them for athletes, emphasizing recovery methods to reduce fatigue, and studying functional variables before and after fatigue.